The storm [large type] - Hawkins, Rachel, 1979- (Thorndike Press large print top shelf., 2026)
"St. Medard's Bay, Alabama, is famous for three things: the deadly hurricanes that regularly sweep into town; the Rosalie Inn, a century-old hotel that's survived every one of those storms; and Lo Bailey, the local girl infamously accused of the murder of her lover in 1984. When Geneva Corliss, current owner of the Rosalie Inn, hears a writer is coming to town to research the crime that put St. Medard's Bay on the map, she's interested in how a successful true crime book might help the struggling inn's bottom line. But as the summer heats up and another monster storm begins, Geneva learns that some people can be just as destructive--and deadly--as any hurricane"--